To solve the equation, we want to isolate the variable x.
First, let's simplify the equation by multiplying both sides by 3 to eliminate the denominators:
(3)(5/3 x + 11/3) = (3)(-4/3)
This simplifies to:
5x + 11 = -4
Next, subtract 11 from both sides of the equation:
5x + 11 - 11 = -4 - 11
Which simplifies to:
5x = -15
Finally, divide both sides of the equation by 5 to solve for x:
(1/5)(5x) = (1/5)(-15)
This yields:
x = -3
Therefore, the solution to the equation is x = -3.
5/3 x + 11/3 = -4/3
7 answers
so 5/3x =???
5/3x is the same as (5/3) * x. It represents the product of 5/3 and x.
5/3x = ?
subtract 11/3 from both sides
subtract 11/3 from both sides
To isolate 5/3x, we can subtract 11/3 from both sides of the equation:
5/3x + 11/3 - 11/3 = -4/3 - 11/3
This simplifies to:
5/3x = -15/3
Now, let's simplify -15/3:
5/3x = -5
Therefore, the equation 5/3x - 11/3 = -4/3 is equivalent to 5/3x = -5.
5/3x + 11/3 - 11/3 = -4/3 - 11/3
This simplifies to:
5/3x = -15/3
Now, let's simplify -15/3:
5/3x = -5
Therefore, the equation 5/3x - 11/3 = -4/3 is equivalent to 5/3x = -5.
tanks
You're welcome! If you have any more questions, feel free to ask.